Unconventional marketing : exploring guerrilla marketing dimension in influencing consumer purchase intention /cby Asnili Marniwati Ahmad - Asnili Marniwati Ahmad (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2013)
Providing business managers with the right perception and preference of consumers are essentials determinants for the success of marketing activities. The research study will also be instrumental in providing insight on how guerrilla marketing utilizes theory of planned behavior (TPB) in reaching targeted groups and provide useful literature for academic purposes as well. Above all, the main study identifies the important dimensions of guerrilla marketing in influencing consumer purchase intention during the marketing process as part of the emergence practices in unconventional marketing. In order to achieve this goal, we propose a general model of guerrilla marketing concept with four dimensions, which we constructed by expanding prior research in marketing in order to reflect the dimensions or characteristics of guerrilla marketing. We hypothesize that the four dimensions are positively related to consumer purchase intention, and that their relative importance varies according to consumer perceptions. To validate the hypothesized model, we conducted a survey with 240 residents using self-administered questionnaires throughout Kuala Lumpur and Klang Valley areas, aged between 18 – 29 years old but only 200 samples of respondents are usable. An empirical test is performed using Exploratory Factor Analysis (EFA), Multiple Regression Analysis and Correlation Analysis. The results show an accepted reliability of EFA and all the four dimensions have a significant effect with customers purchase intention.